Innovative Accounting Solution: A Web-Based Approach for Apotek Saka Sasmitra Using the Waterfall Method - Yuvisan, Evaditus Kresna; Widiantoro, Albertus Dwiyoga; Chrismastuti, Agnes Advensia (Journal of Business and Technology, 2024)
Klinik Saka Sasmitra a healthcare facility that provides medical services, including general practitioners, dentists, and a pharmacy. The pharmacy in this clinic dispenses medications with or without a doctor's prescription. The research focuses on the pharmacy because the process of recording transactions, purchases, and medication inventory is done manually using paper and Microsoft Excel, resulting in inventory management challenges. The clinic conducts numerous transactions per day but lacks an appropriate accounting system and financial reporting. To address this issue, this research proposes the development of an accounting system using the Waterfall method. This method sequences the stages of analysis, design, implementation, testing, improvement, and maintenance to reduce errors. The web-based development will integrate the sales, purchase, and inventory systems and provide financial reports accessible through a web browser. The aim of this design is to provide convenience for both company management and consumers. The research will result in a web-based system for sales, purchase, inventory, and company dashboards.